GRANULOMATOUS PROSTATITIS MASQUERADING AS ADVANCED PROSTATE CANCER: A DIAGNOSTIC CHALLENGE - Masood, Saad; Caratella, Sanya; Kass, Antoine (Journal of Ayub Medical College Abbottabad, 2024)
Granulomatous prostatitis (GP) is a rare inflammatory condition, accounting for only 3.3% of all benign inflammatory lesions of the prostate. Histologically, it is characterized by granulomas secondary to infection, iatrogenic causes, or systemic granulomatous diseases. Most cases are idiopathic and termed nonspecific granulomatous prostatitis (NSGP). First described in 1943 by Tanner and McDonald, GP has an estimated incidence of 0.65–1.5% among inflammatory prostate lesions.